answersLogoWhite

0


Best Answer

2a+6b

User Avatar

Wiki User

โˆ™ 2010-04-17 02:23:12
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar

Add your answer:

Earn +20 pts
Q: Simplify fully 4a plus 5b minus 2a plus b?
Write your answer...
Submit
Related questions

Simplify 9a plus 8 minus 2a minus 3 minus 5a?

2a+5


Simplify 2a plus 11a minus 5a?

2a + 11a - 5a = 8a


Combine like terms and simplify 2b plus 2 minus 2a plus a squared 3?

There are no like terms here.


9a plus 8 minus 2a minus 3 minus 5a?

2a-5


Simplify 4a plus 7b plus 6a-3b-2a?

11a+7b-(3b-2a)


Simplify the answer of 4a plus b-2a-2b?

It is 2a-b simplified


How do you simplify 2a plus 5a?

Add them together: 2a+5a = 7a


Simplify 2a plus 3a plus 4 equals?

2a + 3a + 4 = 5a + 4


Simplify 7a plus 2a plus 1?

9a + 1


Simplify 3a plus 5 plus 2a plus 6?

5a + 11


Simplify 3aยฒ plus a-aยฒ plus 5a?

2a² + 6a


What is 7a plus 3b minus 5a minus 2b minus b?

2a


How do you simplify 2a plus 10 plus 5a-2?

2a + 10 + 5a - 2 = (2a + 5a) + (10 - 2) = 7a + 8


What is the answer to Simplify 5a plus 4b-3a?

2a + 4b


Simplify 2a -3 plus 4b - 2a -b -3 plus 5?

2a-3+4b-2a-b-2a-b-3+5 Can be simplified to: 3b-1


What is 2a squared plus 2b squared minus 5ab factored out?

(a - 2b)(2a - b)


Simplify 2a plus 3b plus 5a plus 6 plus 3b?

6+7a+6b


Simplify the expression 2a -3 plus 4b - 2a -b -3 plus 5?

3b -1


Factor 6a-8ab plus 2a?

6a to the second power minus 8ab + 2a


How do you factor 2a2 plus 2a minus 84?

2(a + 7)(a - 6)


What is 2a minus a?

2a - a = a


Simplify 5aยณ - 4ab plus 2aยณ as much as possible?

5a³ - 4ab + 2a³ = (5+2)a³ - 4ab = 7a³ - 4ab.


What is a if the square root of 4a squared equals 21?

sqrt(4a2) = 21plus or minus (2a) = 21plus or minus (a) = 10.5a = +10.5a = -10.5


What expression is equivalent to 5a plus 8 minus 2a plus 4?

(5a+8) - (2a+4) =3a +4 To do this, simply subtract like terms. 5a-2a=3a and 8-4=4


How do you simplify an expression in the format of 4a2 plus 4ab - y2 plus b2?

4a2 + 4ab - y2 + b2 You cannot simplify this expression because it does not contain like terms, but you can factor it such as: 4a2 + 4ab - y2 + b2 = (4a2 + 4ab + b2) - y2 = (2a + b)2 - y2 = [(2a + b) - y][(2a + b) + y]

People also asked

Factorise 4a plus 6b-12?

View results